2019
DOI: 10.1111/jfbc.13046
|View full text |Cite
|
Sign up to set email alerts
|

Citric acid‐enhanced dissolution of polyphenols during soaking of different teas

Abstract: This study examined the dissolution kinetics and antioxidant activity of tea polyphenols during the soaking of white, yellow, green, oolong, black, and dark teas. All these teas were, respectively, soaked with either freshly boiled distilled water (DW) or 10 mmol/L citric acid–water solution. The residue obtained from one extraction was used for the next extraction and this process was performed consecutively 10 times, soaking for 30 s each time. UHPLC‐QqQ‐MS measurement identified epigallocatechin gallate as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Likely, the oxidation of N-ethylglycine generated the glyoxylate, ethylamine and hydrogen peroxide. The production of hydrogen peroxide strengthens the reactive oxygen species scavenging in plants [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Likely, the oxidation of N-ethylglycine generated the glyoxylate, ethylamine and hydrogen peroxide. The production of hydrogen peroxide strengthens the reactive oxygen species scavenging in plants [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…2017; Li et al . 2019). Under salt stress, a foliar spray with citric acid resulted in higher proline content and total phenolic compounds (TPC) in G. barbadense (El‐Beltagi et al .…”
Section: Discussionmentioning
confidence: 99%
“…Upon drought stress, plants accumulate osmolytes and secondary metabolites in leaves in order to alleviate cell damage. Previous studies revealed that exogenous citric acid pretreatment promotes the synthesis of proline and other metabolites, including phenolic compounds, flavonoids and soluble sugars, in response to environmental stress (Kaur et al 2017;Li et al 2019). Under salt stress, a foliar spray with citric acid resulted in higher proline content and total phenolic compounds (TPC) in G. barbadense (El-Beltagi et al 2017), and also increased non-enzymatic antioxidants (TPC and proline accumulation) in H. sabdariffa and Melissa officinalis to maintain redox balance (Ahmed et al 2017;Abdellatif & Ibrahim, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…PCA analysis is an unsupervised statistical model that performs data reconstruction and dimensional reduction methods by means of principal components (PCs; Li et al, 2019). To investigate the difference in the profiles of catechins in Ya'an Tibetan tea, PCA was adopted to analyze the catechin contents of each tea extract.…”
Section: Comparison Of the Contents Of Tea Catechins Of Tibetan Tea With Various Storage Yearmentioning
confidence: 99%